Rethinking drinking and sport : new approaches to sport and alcohol - Palmer, Catherine (Social scientist) (Farnham, Surrey, England ; Burlington, VT : Ashgate, 2015)
This book examines the complex nature of sport-related drinking. With close attention to the contradictory nature of sport-related drinking, this book considers both 'the problem' of drinking in sport, as well as some of the issues for treatment and recovery that sports-related drinking presents. Based on research across a variety of sports in the UK and Australia, Rethinking Drinking and Sport explores not only the relationship between alcohol, fans, participants and industry, but also questions of gender and identity to provide fresh insights into the complex relationships between drinking and sport.
Acknowledgments -- Preface -- Social practices and drinking identities -- Mapping the sport-alcohol nexus -- Beyond hegemonic masculinity -- Women and sport-related drinking -- Non-drinking, dry events and alternative forms of sport -- Biographies of drinking -- Tackling the problem -- Changing the culture -- Some paradoxes and potentials for recovery and prevention -- Policy and sponsorship -- Rethinking drinking and sport -- Bibliography -- Index.
Includes bibliographical references (pages163-187) and index.
Keywords: Drinking of alcoholic beverages; Athletes